Using a Situational Awareness Display to Improve Rider Trust and Comfort with an AV Taxi. (November 2019) - Chang, Chun-Cheng; Grier, Rebecca A.; Maynard, Jason; Shutko, John; Blommer, Mike; Swaminathan, Radhakrishnan; Curry, Reates
There is evidence that a significant portion of the population does not trust automated vehicles (AV). Research on trust in automation suggests that providing insight into how automation functions via a situational awareness (SA) display improves trust. However, it is unclear how much information is needed to build trust. A study was conducted to evaluate what amount of information improves passenger trust with an AV. After a ride in a simulated AV with one of four SA displays with varying amounts of information or no SA display, participants completed questions about trust and comfort. In addition, participants completed a card sorting task to determine what content they desired to see on the SA display. Our conclusions suggests that an SA display engenders trust and comfort. However, such a display should present a low amount of information. A possible explanation is that high information density displays might be more difficult for participants to interpret.